Vaccine management practices among healthcare workers in Morogoro, Tanzania: a cross-sectional study - Bonaventura Nestory; Mackfallen Anasel; Jean Baptiste Nyandwi; Domina Asingizwe (Taylor & Francis Group, 2022)
Background Effective vaccine management is essential to maintain the quality of vaccines, minimise wastages, and prevent missed opportunities for vaccination at service delivery points. Objectives This study aims to assess vaccine management practices among vaccinators at health facilities in the Morogoro region, Tanzania. Methodology A descriptive cross-sectional study design involved health workers from 77 health facilities offering vaccination services. The study population consisted of vaccine handlers and vaccinators working in public health facilities in the Morogoro region. The vaccine management practices were assessed using data collected from ledgers and the Vaccine Information Management System (VIMS). The temperature records were downloaded from the Fridge-tag® 2 and Coldtrace5 devices. Results The findings indicated that 65 (84%) health facilities had functional refrigerators and are using power from 26 (34%), 28 (36%), and 23 (30%) of grid electricity, solar, and Liquefied Petroleum Gas (LPG), respectively. Besides, 27 (35%) health facilities have an alternative energy source as a backup. In general, healthcare workers had a good knowledge of cold chain management, including the World Health Organization recommended storage temperatures for vaccines. Furthermore, vaccine stockout was found in 12 (15.6%) health facilities for at least one antigen and 4 (5.1%) health facilities for all five antigens under observation. This current study also revealed that the average calculated vaccine wastage rates for DTP, Measles-Rubella and Rotavirus vaccines were 7%, 19%, and 15%, respectively. More than half of health workers did not perform monthly temperature data reviews. In addition, poor performance led to high wastage rates, including the Rotavirus vaccines, and a change in VVM to discard points. Finally, a small number of 5 (6.5%) health facilities consecutively reported temperature exposure beyond + 8 Celsius (between 5.9 and 281 h). Conclusions Healthcare workers' vaccine and cold chain management knowledge were good for temperature data reading and documentation. However, the practices were poor for some health facilities. The gaps observed in this study inform health managers and policymakers toward establishing interventions to improve health workers' knowledge and practice, including mentorships, supervision, and training to guarantee that each child in all communities reaps the benefits of immunisation services.